2021
DOI: 10.3389/fpsyt.2021.790745
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Links Between Early Auditory Information Processing and Negative Symptoms in Schizophrenia: An ERP Study

Abstract: Background: Negative symptoms represent a heterogeneous dimension with a strong impact on functioning of subjects with schizophrenia (SCZ). Five constructs are included in this dimension: anhedonia, asociality, avolition, blunted affect, and alogia. Factor analyses revealed that these symptoms cluster in two domains: experiential domain (avolition, asociality, and anhedonia) and the expressive deficit (alogia and blunted affect), that might be linked to different neurobiological alterations. Few studies invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…The resulting combination of EEG alterations, in chronic patients with schizophrenia, was associated with real-life functioning and with illness-related variables which have an impact on functional outcomes, such as cognitive impairment, depression, and negative symptoms, at 4-year follow-up [ 4 , 6 ]. Previous research identified alterations of several EEG indices in SCZs, which are related to different brain functions and associated with different illness features influencing the outcome or with the outcome itself [ 25 29 ]. However, despite the results of these studies, no EEG index has been implemented in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting combination of EEG alterations, in chronic patients with schizophrenia, was associated with real-life functioning and with illness-related variables which have an impact on functional outcomes, such as cognitive impairment, depression, and negative symptoms, at 4-year follow-up [ 4 , 6 ]. Previous research identified alterations of several EEG indices in SCZs, which are related to different brain functions and associated with different illness features influencing the outcome or with the outcome itself [ 25 29 ]. However, despite the results of these studies, no EEG index has been implemented in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several quantitative resting-state EEG and event-related potentials (ERP) alterations have been reported in SCZs in different stages of the illness and many of them are associated with psychopathology, cognitive impairment, and functional outcome [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the MAP domain is associated with deficits in different aspects of motivation [ 1 4 , 6 , 10 , 33 35 , 40 42 ], or general impairment in decision making and executive control of behavior, although this latter hypothesis needs further investigations [ 28 ]. The EXP domain, on the other hand, is associated with impairments in cognition and social cognition and might be subtended by a diffuse neurodevelopmental alteration in brain connectivity leading to deficits in overall cognition [ 1 4 , 6 , 10 , 30 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two-factor solution of negative symptoms has been very influential over time, guiding the way research studies have been conducted to investigate the pathophysiological mechanisms of negative symptoms [ 30 ], the way rating scales are scored in statistical analyses, and the way clinical trials have been designed to develop treatments for these symptoms.…”
Section: Introductionmentioning
confidence: 99%